2010
DOI: 10.1002/chem.200903455
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Experimental/Theoretical Investigation of the Statistical Olefin/Conjugated Diene Copolymerization Catalyzed by a Hemi‐Lanthanidocene [(Cp*)(BH4)LnR]

Abstract: Statistical copolymerization of ethylene and isoprene was achieved by using a borohydrido half-lanthanidocene complex. Under copolymerization conditions, activation of [(Cp*)(BH(4))(2)Nd(thf)(2)] (Cp*=η(5)-C(5)Me(5)) by an appropriate alkylating agent affords trans-1,4-poly-isoprene-co-ethylene. Analysis of the microstructure of the copolymer revealed the presence of successive short sequences of ethylene/ethylene, trans-1,4-isoprene/ethylene, and trans-1,4-isoprene/trans-1,4-isoprene. A small amount of 1,2-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 78 publications
(45 reference statements)
1
43
1
Order By: Relevance
“…More recently, ethylene–isoprene copolymerization with half‐metallocene and nonmetallocene organometallic catalysts have been reported . Rare‐earth organometallic catalysts have been found to be capable of catalyzing ethylene/conjugated diene copolymerizations, but the products usually contain higher conjugated diene units than ethylene . There have been no literature reports on ethylene/conjugated diene copolymerizations catalyzed by supported Ziegler–Natta catalysts or supported metallocene catalysts that are currently used in industrial production of polyethylene resins.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, ethylene–isoprene copolymerization with half‐metallocene and nonmetallocene organometallic catalysts have been reported . Rare‐earth organometallic catalysts have been found to be capable of catalyzing ethylene/conjugated diene copolymerizations, but the products usually contain higher conjugated diene units than ethylene . There have been no literature reports on ethylene/conjugated diene copolymerizations catalyzed by supported Ziegler–Natta catalysts or supported metallocene catalysts that are currently used in industrial production of polyethylene resins.…”
Section: Introductionmentioning
confidence: 99%
“…In view of their stronger Lewis acidity,t herefore, we expected graphene-supported La complexes to act as active polymerization catalysts and we decided to study their catalytic activity in the homo-a nd co-polymerization of ethylene and 1,3-butadiene. [58,[68][69][70][71][72] Ethylenep olymerization…”
Section: Probing the Lewis Acidity Of Graftedcomplexes:o =Pph 3 Coordmentioning
confidence: 99%
“…Lanthanide-based molecular complexes, finally,a lso lead to the formation of mainly 1,4-cis polybutadiene polymers,m olecular catalysts showing both high activity and trans-1,4-selectivity being rathers carce. [68,69,72,73] Ethylene 1,3-butadiene co-polymerization…”
Section: 3-butadiene Polymerizationmentioning
confidence: 99%
“…Lowering the reaction temperature ( T =−10 °C) made the polymerization more controllable and the cis ‐1,4‐selectivity increased to 97.2 % and molecular weight distribution down to 1.7 . The DFT calculations revealed that catalytic activity and stereoselectivity on the ternary system were controlled by kinetic favorable transition state of intermediate formed by initiator and monomer . In 2009, Hou and co‐workers reported a series of scandium dialkyl complexes: Cp′Sc(CH 2 SiMe 3 ) 2 (THF) (Cp′=C 5 H 5 ( 61 ), C 5 MeH 4 ( 62 ), C 5 Me 4 H ( 63 ), C 5 Me 5 ( 64 ), C 5 Me 4 SiMe 3 ( 4 Sc )) and CGC complexes, (C 5 Me 4 R)Sc(CH 2 SiMe 3 ) 2 (R=CH 2 CH 2 PPh 2 ( 65 ), C 6 H 4 OMe‐ o ( 22 )) .…”
Section: Stereoselective Polymerization Of Conjugated Dienesmentioning
confidence: 99%